15‐1: Novel Multi‐Frequency Driving of OLED for Low Power Consumption. Issue 1 (28th June 2022) - Kwon, Sangan; Kim, Soondong; Yoon, Changnoh; Kim, Taehoon; Yang, Jinwook; Choi, Yongseok; Choe, Wonjun
Abstract : In a recent, OLED display has been required to larger and higher resolution by the years. So, display image quality and power consumption are getting important. It is necessary to reduce power consumption to increase battery usage time. Low frequency driving is the significant factor for long‐term use. We can operate low frequency driving using oxide TFT with small leakage current. However, the low frequency driving operates when the entire screen is a still image. To improve power consumption, we propose Multi‐Frequency Driving (MFD) technology. MFD is a technology that divides moving and still image areas in full screen display and drives them at different frame frequency. In this paper, we suggest what MFD technology is and how to implement the OLED driving system. And then we show how much it can improve power consumption for OLED.